Human Resource Competency Development in the Education Sector through Classroom Action Research (CAR) - Aulia Shafira Vanessa (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital technology and the utilization of Artificial Intelligence (AI) in education have brought significant changes to the learning process in higher education institutions. On the one hand, technology provides easier access to information and supports the effectiveness of learning activities; on the other hand, it also creates challenges related to academic integrity and students’ critical thinking skills. This condition highlights the need for human resource competency development in the education sector through adaptive, innovative, and academically oriented learning strategies. This study aims to analyze the development of educational human resource competencies through the implementation of Classroom Action Research (CAR) in the SMART–Integrity Learning (SMILE) strategy among students of the Faculty of Economics at Sriwijaya University. The study employed a descriptive qualitative approach using the Classroom Action Research method, which was conducted through the stages of planning, action, observation, and reflection. The research subjects were students of the Faculty of Economics at Sriwijaya University enrolled in courses taught by the researcher. Data collection techniques included classroom observation, documentation of student assignments, evaluation of Turnitin and AI Detector results, and learning reflections. The findings indicate that the implementation of the SMILE strategy successfully increased students’ awareness of academic integrity through the application of a maximum similarity limit of 25%, enhanced critical thinking skills through case-based discussions and the use of AI as a learning partner, and improved students’ active participation in the learning process. This study demonstrates that the development of educational human resource competencies can be achieved through adaptive, collaborative, and academically ethical learning innovations to support more effective and professional learning quality.